2022
DOI: 10.3389/fimmu.2022.923235
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of interstitial macrophages in pulmonary fibrosis: A perspective from scRNA-seq analyses

Abstract: Pulmonary fibrosis is an irreversible and progressive disease affecting the lungs, and the etiology remains poorly understood. This disease can be lethal and currently has no specific clinical therapeutic regimen. Macrophages, the most common type of immune cell in the lungs, have been reported to play a key role in the pathogenesis of fibrotic disease. The lung macrophage population is mostly composed of alveolar macrophages and interstitial macrophages, both of which have not been thoroughly studied in the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 92 publications
(155 reference statements)
1
8
0
Order By: Relevance
“…[ 41 ] Meanwhile, a recent study showed that β‐glucan elicits lung interstitial macrophage training and that lung interstitial macrophages play a crucial role in PF. [ 40 , 45 ] In our single cell RNAseq analysis of whole lungs of untrained and β‐glucan‐trained mice, the relative number of interstitial macrophages (F4/80, CD11b, CX3CR1; CX3CR1, CCR2, MafB, MHCII [H2‐Eb1, H2‐Aa, and H2‐Ab1]) in the lungs of trained mice underwent dynamic alterations during the course of lung injury (data not shown). On day 4 after the sham/bleomycin instillation, there was an increase in lung interstitial macrophages of trained mouse in the absence of injury.…”
Section: Discussionmentioning
confidence: 95%
“…[ 41 ] Meanwhile, a recent study showed that β‐glucan elicits lung interstitial macrophage training and that lung interstitial macrophages play a crucial role in PF. [ 40 , 45 ] In our single cell RNAseq analysis of whole lungs of untrained and β‐glucan‐trained mice, the relative number of interstitial macrophages (F4/80, CD11b, CX3CR1; CX3CR1, CCR2, MafB, MHCII [H2‐Eb1, H2‐Aa, and H2‐Ab1]) in the lungs of trained mice underwent dynamic alterations during the course of lung injury (data not shown). On day 4 after the sham/bleomycin instillation, there was an increase in lung interstitial macrophages of trained mouse in the absence of injury.…”
Section: Discussionmentioning
confidence: 95%
“…Whole lung microarray and gene clustering analysis highlighted a collective upregulation of pro-inflammatory and fibrosis genes in the Erg-CKO lungs. High infiltration of LY6C+ monocytes 30 , cDC1 antigen presentation cells 54 , and anti-inflammatory interstitial macrophages 32 collectively suggested an increased inflammatory predisposition in Erg-CKO lungs. Upregulation of key fibrotic genes (Ccn2, Pai1) and inflammatory genes (Tgfβ, Ifnγr1 and Ifnγr2) in Erg-CKO lung further indicated a possible predisposition to fibrosis [55][56][57][58][59] .…”
Section: Discussionmentioning
confidence: 99%
“…41 These results in spatial levels, support that fibroblast and infiltrated macrophages were key pathology players in PCPFs. and pirfenidone effectively reversed the expression of lung fibrosisrelated genes, including syndecan-2 (SDC2), 42 PLA2G7, 43 and serpin family G member 1 (SERPING1), 44 common to COVID-19, IPF, and TGF-β1-induced lung fibrosis transcriptomes.…”
Section: Discussionmentioning
confidence: 99%
“…We analyzed the impact of antifibrotic drugs on the transcriptome of a rat model of TGF‐β1‐induced lung fibrosis. Nintedanib, sorafenib, and pirfenidone effectively reversed the expression of lung fibrosis‐related genes, including syndecan‐2 ( SDC2 ), 42 PLA2G7 , 43 and serpin family G member 1 ( SERPING1 ), 44 common to COVID‐19, IPF, and TGF‐β1‐induced lung fibrosis transcriptomes.…”
Section: Discussionmentioning
confidence: 99%